3a+5-(-6a+4)=-(8a-1)

Simple and best practice solution for 3a+5-(-6a+4)=-(8a-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a+5-(-6a+4)=-(8a-1) equation:



3a+5-(-6a+4)=-(8a-1)
We move all terms to the left:
3a+5-(-6a+4)-(-(8a-1))=0
We get rid of parentheses
3a+6a-(-(8a-1))-4+5=0
We calculate terms in parentheses: -(-(8a-1)), so:
-(8a-1)
We get rid of parentheses
-8a+1
Back to the equation:
-(-8a+1)
We add all the numbers together, and all the variables
9a-(-8a+1)+1=0
We get rid of parentheses
9a+8a-1+1=0
We add all the numbers together, and all the variables
17a=0
a=0/17
a=0

See similar equations:

| x^2−3x+8=0 | | 4x-24/2=4 | | x-0.01=0.1 | | 4x(5x-10)=3(3x+2) | | -2x^2+18=12x | | 7m+12=(-4m)+78 | | 2x+3×=36 | | 5x+12-2x+15=6x-3+x+1 | | 3x+15=5x-20 | | 1-3x=-2x-5 | | 8x+3=6- | | x+3=30x2 | | (3y+1)=9 | | .1x+x=23.78 | | 0.2016=0.277-0.0056x+0.0000478x^2 | | 7x+2=5175 | | x2-6x-41=0 | | 4x-6-2x/3=4x+6x-3 | | 6m(m)-20=9m | | V(x)=x(8-2x)(5-2x) | | 10y^2-15y-54=0 | | 3(x2-2)=66 | | 3x-5/5-x-3/2=2(x+5) | | 6a=1=3a+10 | | 0.3x-0.25x=-1.375 | | (70y2–3y–54=0) | | 3a+4(a-2)=12-(8-3a) | | 9y+15=820 | | (2x+5)(2x-3)=0 | | 9a+6+2(3a+5)=0 | | 6y-2=8+2y | | X^2+8x16=0 |

Equations solver categories